Behçet’s disease risk association fine-mapped on the IL23R–IL12RB2 intergenic region in Koreans - Kang, Eun Ha (Arthritis Res Ther, 2017)
BACKGROUND: Behçet’s disease (BD) susceptibility had been associated with single-nucleotide polymorphisms (SNPs) in IL23R–IL12RB2, IL10, STAT4, or ERAP1 locus in Japanese, Turkish, Chinese, and other populations, but not in a Korean genome-wide association study (GWAS). We aimed to fine-map BD risk association of these four loci using extensive imputation and additional genotyping for replication. METHODS: In the discovery phase, 369 patients with BD enrolled in the previous Korean GWAS and 2000 controls retrieved from a population-based cohort of healthy Koreans were imputed for their genotypes of all SNPs in the four loci using the Asian data of the 1000 Genomes Project as reference. For genotype imputation of ERAP1 SNPs, the adjacent ERAP2 SNPs were also covered. For the 10 most significantly associated SNPs (8 imputed and 2 GWAS-genotyped), an additional 84 patients with BD and 283 healthy controls were genotyped for replication. The results from the discovery and replication phases were pooled for meta-analysis using the Mantel-Haenszel test to estimate the odds ratio (OR) and 95% confidence interval (CI). RESULTS: An IL23R–IL12RB2 intergenic SNP rs1495965 was significantly associated with BD risk (OR (95% CI) = 1.5 (1.3, 1.7), P = 2.5 × 10(−7)) in the pooled meta-analysis of the discovery (1.4 (1.2, 1.7), P = 4.9 × 10(−7)) and replication (1.9 (1.3, 2.6), P = 6.0 × 10(−4)) phases. BD risk association was fine-mapped on the intergenic region rather than the two flanking genes, as rs1495966 and rs4655535, almost perfectly correlated with rs1495965 (r (2) = 0.99), were also located in the same intergenic region. Consistent with previous reports, the P values tended to be lower within IL23R than IL12RB2. On the other hand, several IL10 SNPs were suggested for association in the discovery phase but all failed in the replication phase. No SNP in ERAP1–ERAP2 and STAT4 was suggested even in the discovery phase. CONCLUSIONS: BD susceptibility association was fine-mapped on the intergenic region between IL23R and IL12RB2 as marked by three correlated SNPs, rs1495965, rs1495966, and rs4655535. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-017-1435-5) contains supplementary material, which is available to authorized users.